National culture and dividend policy - Shao, Liang; Kwok, Chuck CY; Guedhami, Omrane (Journal of International Business Studies, 2010)
This interdisciplinary study examines how national culture affects corporate dividend policies. The dividend puzzle is one of the most studied, yet unresolved, issues in financial economics. Prior theoretical and empirical research has suggested several explanations of the dividend puzzle that are rooted mainly in agency, asymmetric information, “bird in hand”, and pecking order theories. The main intuition behind our analysis is that dividend policy may be determined not only by an objective assessment of the severity of agency and asymmetric information problems within a firm, but also by management's and investors’ subjective perceptions of these problems, which hinge on their national culture. Using Schwartz's national culture dimensions, Conservatism and Mastery, we find that Conservatism is positively related and Mastery negatively related to dividend payouts for a sample of 27,462 firm-years from 21 countries between 1995 and 2007. These effects are robust to controls for a wide variety of other determinants of dividend policy – including investor protection, stock market performance, financial system configuration, tax advantage, economic development, and dividend catering premium – and to alternative culture proxies and sub-period windows. Our findings that national culture affects perceptions of and responses to agency and information asymmetry have important implications for policymakers and multinational enterprises.